Control Interno Y Su Incidencia En La Productividad De La Compañía De Transporte De Carga Pesada Ciudad Del Río Cideriosa S. A. Cantón Quevedo, Año 2023 - Barahona Loor, Elsa Mariela (2025)
The study analyzes internal control in route planning and operational management of the Heavy Cargo Transportation Company Ciudad del Río CIDERIOSA S.A., aiming to evaluate its impact on productivity. Based on the COSO IV model, risk management and regulatory compliance were examined. A mixed methodology (quantitative and qualitative) was applied, using inductive, deductive, and descriptive methods. Data collection techniques included observation and narratives, along with instruments such as questionnaires, indicators, and flowcharts. The analyzed variables include route planning, regulatory compliance, safety, customer service, fleet allocation, and maintenance management. The results show a positive performance in route planning, fleet allocation, and maintenance, with 100% compliance in route execution and an average efficiency of 26.25 minutes per. However, deficiencies were identified in incident prevention (60% compared to a 90% standard) and in the execution of customer requests (73.26%). Internal control has improved efficiency and operational safety, but real-time monitoring and process digitization need to be optimized. It is recommended to implement a digital fleet management system, strengthen security training, and enhance customer service through better resource allocation.